Variants of the Monoamine Oxidase A Gene (MAOA) predict free-riding behavior in women in a strategic public goods experiment - Vanessa Mertins; Andrea B. Schote; Jobst Meyer (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
Laboratory experiments have documented substantial heterogeneity in social preferences, but little is known about the origins of such behavior. Previous research on public goods experiments suggests that individual-level demographic and psychological variables correlate with player types. However, the key question about biological sources of variation in these preferences remains open. The aim of this study is to uncover genetic variations that influence differences in cooperative behavior. For this reason, we identify types of players within a strategic public goods experiment. We explicitly test for an association between individual variance in strategy choice and the functional promoter-region repeat of the monoamine oxidase A gene (MAOA). Our experimental findings suggest a link between MAOA and the occurrence of free-riding in females. Females with MAOA-L are less likely to behave like weak free-riders than MAOA-H carriers, whereas among males, our results did not support a significant relation between genotype and player type. Furthermore, MAOA-L female carriers contribute more than MAOA-H subjects to the public good if they know that others contribute nothing, and they showed slightly lower scores on the Machiavellianism scale. This is the first piece of evidence that genotype might predict player type within a public goods setting. It contributes to our understanding of biological drivers of economic decision-making and points to the need for further exploration.
Keywords: H41; D87; C91; C72; 330; gene; player type; public good; conditional cooperation; experimental economics